THE CORRELATION BETWEEN SERUM PSA LEVEL AND PROSTATE HISTOLOGIC AGGRESSIVENESS WITH PROSTATIC VOLUME IN BPH PATIENTS - Duarsa, Gede Wirya Kusuma; Oka, AA Gde; Santosa, Kadek Budi; Yudiana, Wayan; Tirtayasa, Pande Wisnu; Udiyana, Nyoman Dwi Maha; Mahadewa, Tjok Gede Bagus (Indonesian Urological Association, 2019)
Objective: Prostate inflammation is one of pathophysiology of prostate hyperplasia in benign prostatic hyperplasia (BPH). There are several factor that involved in prostatic inflammation, such as prostate specific antigen (PSA) that play a role as an autoantigen. The objective of this study was to assess the correlation between free PSA level with prostate histologic aggressiveness, and also the correlation between prostate histologic aggressiveness with prostatic volume in BPH patients. Material & Methods: The design of this study was cross-sectional analytic observational study to determine correlation between serum PSA level with prostatic aggressiveness, and prostatic volume with prostatic aggressiveness. This study was performed from June to November 2016 in Sanglah Public Hospital, Surya Husadha, Balimed, Bhakti Rahayu, and Ganesa Hospital. Eighty three patients with BPH undergoing transurethral resection of the prostate (TURP) were recruited. Results: The result of gamma correlation analysis using Chi-square of PSA level with aggressiveness (p=0.000) and aggressiveness with prostatic volume (p=0.012). Conclusion: Serum PSA level were correlated with prostatic aggressiveness. Prostatic aggressiveness also correlated with prostatic volume.